2018
DOI: 10.7150/thno.23180
|View full text |Cite
|
Sign up to set email alerts
|

Genes involved in prostate cancer progression determine MRI visibility

Abstract: MRI is used to image prostate cancer and target tumors for biopsy or therapeutic ablation. The objective was to understand the biology of tumors not visible on MRI that may go undiagnosed and untreated.Methods: Prostate cancers visible or invisible on multiparametric MRI were macrodissected and examined by RNAseq. Differentially expressed genes (DEGs) based on MRI visibility status were cross-referenced with publicly available gene expression databases to identify genes associated with disease progression. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 30 publications
5
50
0
Order By: Relevance
“…Centromere protein F (CENPF), a transient kinetochore protein, exhibits a cell-cycle dependent localization, and is completely degraded at the end of cell division (4)(5)(6). Evidence has shown that CENPF is overexpressed in head and neck squamous cell carcinomas, hepatocellular carcinoma, breast cancer and prostate cancer, and it may be a prognostic marker for these cancers (7)(8)(9)(10)(11)(12). Forkhead box M1 (FOXM1) is a typical proliferation-associated factor and plays an important role in development (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Centromere protein F (CENPF), a transient kinetochore protein, exhibits a cell-cycle dependent localization, and is completely degraded at the end of cell division (4)(5)(6). Evidence has shown that CENPF is overexpressed in head and neck squamous cell carcinomas, hepatocellular carcinoma, breast cancer and prostate cancer, and it may be a prognostic marker for these cancers (7)(8)(9)(10)(11)(12). Forkhead box M1 (FOXM1) is a typical proliferation-associated factor and plays an important role in development (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…As a regulator of chromosome segregation, CENPF is expressed in a cell cycle-dependent manner; it gradually accumulates during the cell cycle, reaches peak levels in the G 2 /M phase, and then degrades upon completion of mitosis [16]. CENPF is upregulated in PC and plays an important part in malignant progression [17,18]. Interestingly, CENPF also significantly enhances chemotherapeutic sensitivity [19].…”
Section: Introductionmentioning
confidence: 99%
“…This comprehensive analysis provides a valuable opportunity to better understand the biochemical changes underlying cancer metabolism and improve early detection, progression, and therapeutic monitoring . Metabolomics can also respond to clinical challenges by providing a method of detecting vital and promising novel biomarkers . In terms of cancer, metabolomics can enable additional measurement of downstream activities, thereby allowing for the discovery of key oncometabolites .…”
Section: Introductionmentioning
confidence: 99%